(untitled) (Baghdad Science Journal, 2019)
In this work, synthesis of conducting polymeric films namely, PVC thin films was carried out containing Schiff base (L) with Cu2+, Cr3+, Ni2+, Co2+, in addition to inspecting the possibilities of measuring energy gap values of PVC-L-M with variety metal ions. These new polymeric films (PVC-L-M) were characterized by FTIR spectrophotometry, energy gap and surface morphology. The optical data recorded that the band gap values are influenced by the type of metals. All modified films have a red shift in optical properties in the ultraviolet region. The PVC-L-Co(II) was the lowest value of the optical band gap, 3.1 eV.